2000
DOI: 10.1091/mbc.11.4.1213
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Membrane Proteins Are Transported in Distinct Carriers: A Two-Color Video Microscopy Study in Cultured Hippocampal Neurons

Abstract: Neurons transport newly synthesized membrane proteins along axons by microtubule-mediated fast axonal transport. Membrane proteins destined for different axonal subdomains are thought to be transported in different transport carriers. To analyze this differential transport in living neurons, we tagged the amyloid precursor protein (APP) and synaptophysin (p38) with green fluorescent protein (GFP) variants. The resulting fusion proteins, APP-yellow fluorescent protein (YFP), p38-enhanced GFP, and p38-enhanced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
227
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(280 citation statements)
references
References 44 publications
48
227
3
Order By: Relevance
“…APP delivery to the axon makes use of the fast axonal transport system Sisodia et al 1993), with kinesin-1 as the microtubule motor protein (reviewed in Kins et al 2006). As visualized by GFP-tagged fusion proteins, APP is transported in vesicular and often elongated tubular structures which move with special characteristics along the axon (Kaether et al 2000;Stamer et al 2002;Goldsbury et al 2006;Szodorai et al 2009). Whereas most other proteins are axonally transported in vesicles that display a saltatory movement, often changing directions, the APP tubules continuously move unidirectionally, with an average speed of 4.5 mm/s, reaching maximal speeds up to 10 mm/s (Kaether et al 2000).…”
Section: Trafficking Of App In Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…APP delivery to the axon makes use of the fast axonal transport system Sisodia et al 1993), with kinesin-1 as the microtubule motor protein (reviewed in Kins et al 2006). As visualized by GFP-tagged fusion proteins, APP is transported in vesicular and often elongated tubular structures which move with special characteristics along the axon (Kaether et al 2000;Stamer et al 2002;Goldsbury et al 2006;Szodorai et al 2009). Whereas most other proteins are axonally transported in vesicles that display a saltatory movement, often changing directions, the APP tubules continuously move unidirectionally, with an average speed of 4.5 mm/s, reaching maximal speeds up to 10 mm/s (Kaether et al 2000).…”
Section: Trafficking Of App In Neuronsmentioning
confidence: 99%
“…This is among the fastest transport velocities measured in cultured neurons. Significant retrograde transport with slightly slower kinetics was also observed (Kaether et al 2000;Stamer et al 2002). Little is known about the fate of the axonal transport carrier vesicles.…”
Section: Trafficking Of App In Neuronsmentioning
confidence: 99%
“…It has been previously established that APP exits the TGN in polarized and nonpolarized cells by using the basolateral sorting machinery (Haass et al, 1994;Simons et al, 1995;Tienari et al, 1996a,b;Kaether et al, 2000), so it can be found on post-Golgi carriers costaining with markers of this pathway, including VSVG protein. Results in our laboratory using HeLa, Chinese hamster ovary, or primary cultured mouse hippocampal neuronal cells have confirmed these findings (data not shown).…”
Section: Knockdown Of Mint3 Alters App Trafficmentioning
confidence: 99%
“…To label presynaptic synapses (output synapses), we used a synaptophysin:GFP fusion protein. Synaptophysin:GFP was the first synaptic vesicle protein to be cloned and has been extensively used to study the distribution and density of presynaptic sites in neurons both in vitro and in vivo (17)(18)(19)(20)(21)(22).We labeled progenitors for GC neurons with these genetic markers to visualize their synapse development, and observed that in adult-generated neurons, PSD-95:GFP-positive clusters (PSD ϩ C) developed initially at high density in the proximal 15% of the unbranched apical dendrite. We therefore defined the proximal 15% of the unbranched apical dendrite as the proximal domain.…”
mentioning
confidence: 99%
“…To label presynaptic synapses (output synapses), we used a synaptophysin:GFP fusion protein. Synaptophysin:GFP was the first synaptic vesicle protein to be cloned and has been extensively used to study the distribution and density of presynaptic sites in neurons both in vitro and in vivo (17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%